If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 8y = -9 Solving -9x + 8y = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. -9x + 8y + -8y = -9 + -8y Combine like terms: 8y + -8y = 0 -9x + 0 = -9 + -8y -9x = -9 + -8y Divide each side by '-9'. x = 1 + 0.8888888889y Simplifying x = 1 + 0.8888888889y
| 4+5x=2*(5+4x) | | 4+3x=6x-26 | | -6=2y-9 | | 3x-9=-4x-37 | | -5-4x=23 | | 10y+4=6y | | -7-4x=-3x-14 | | 4t+1=24 | | 3z+7=4 | | 6x+8=-6x-112 | | V+45-5v=-34 | | 12r+6r=11p-10 | | -34=1-x-12 | | -7.8=4.4+2.4 | | 10x+5=10x | | 7x-9=27+4x | | 3x+6=-4x+20 | | 4b=11-7b | | 1-7x=6x+92 | | 0.5x+55=200 | | 0.5x+55=30 | | 7+4n+6n=-13 | | 0.5+55=30 | | 7.5+0.02x=9.5+0.01x | | a-5b-3ac= | | f(-2)=2x+3 | | 5a-15+9=3a+29 | | 71+4n+4=-14n-15 | | 2m^2-28m+49=0 | | 6.44x+325=2500 | | 9*7+8*x-2=93 | | 2s+3t=43 |